Frameworks to envision equitable urban futures in a changing climate: A multi-level, multidisciplinary case study of New York City - Balk, Deborah; Tagtachian, Daniela; Jiang, Leiwen; Marcotullio, Peter; Cook, Elizabeth M.; Jones, Bryan; Mustafa, Ahmed; McPhearson, Timon (Frontiers in Built Environment, 2022)
Cities are at the forefront of climate-change action and planning for futures that are concomitantly more resilient and equitable, making local goals imperative for global sustainability. Under the twin challenges of changing climatic and socioeconomic conditions, cities need the means to meet these goals. As places with concentrated and diverse populations, socioeconomic vulnerability, and amplified exposure, cities are responsible for most of the world’s greenhouse gas emissions. Yet, much is unknown and intrinsically uncertain about the range of plausible urban futures, which have differing implications for both potential mitigation and adaptation actions. To better assess these plausible futures, the global-change research community developed the Shared Socioeconomic Pathways (SSPs) framework for global and regional policy. Importantly, this global-scale framework does not include specific city-level perspectives or data at the spatial scales necessary to address questions of local relevance. While the SSPs address many of the key population and socioeconomic drivers of climate change, they do not address important concerns especially relevant to cities, such as racial justice or migration status. Nevertheless, city-level impacts will evolve, in part, as a function of the global-scale change characterized by the SSPs, and in part, based on demographic and social processes already underway. Modifying this framework to cities, therefore, has the potential to help limit local climate impacts, and create a more resilient, equitable city. To address these needs and respond to city/regional stakeholders, we propose a framework for science-based narratives and quantitative projections, using New York City and the metropolitan region as a case study. We review a wide-range of existing approaches to generating estimates of future populations and identify their vulnerabilities to climate-change hazards ranging from: subnational population projections, spatially-explicit allocation of populations linked to SSPs for the US and selected cities; city-specific population forecasting without climate considerations, and participatory approaches to future scenario development and fine-scale, within-city land-use change models. By showcasing the strengths and limitations of various methods, their spatial and temporal scales, and thematic breadth, we propose a novel framework that leverages state-of-the art quantitative approaches and couples it with stakeholder engagement that can help cities plan equitably under uncertainty.